RNA Biopesticides: A Cutting‐Edge Approach to Combatting Aquaculture Diseases and Ensuring Food Security - Qiu Li; Lixing Huang (Modern Agriculture)
ABSTRACT Aquaculture plays a crucial role in addressing global nutritional demands and economic growth. However, the high‐density nature of aquaculture presents significant challenges, including disease outbreaks that hinder production and impact profitability. Diseases are a major concern, with losses exceeding 25%, and new pathogens emerging each year. Traditional pharmaceuticals struggle with drug resistance and environmental harm, raising food safety concerns due to chemical residues. RNA‐based biopesticides offer a promising solution by targeting specific mRNA sequences in pathogens, thereby inhibiting their growth and reproduction. These biopesticides, including siRNA and dsRNA, have shown great potential in managing aquaculture diseases. With high specificity and minimal environmental impact, RNA biopesticides provide an innovative, sustainable approach to combating diseases in aquaculture, enhancing both food security and environmental safety.